Independent Emergence of the Cosmopolitan Asian Chikungunya Virus, Philippines 2012 - Tan, Kim-Kee; Sy, Ava Kristy D.; Tandoc, Amado O.; Khoo, Jing-Jing; Sulaiman, Syuhaida; Chang, Li-Yen; AbuBakar, Sazaly (Scientific reports, 2015)
Outbreaks involving the Asian genotype Chikungunya virus (CHIKV) caused over one million infections in the Americas recently. The outbreak was preceded by a major nationwide outbreak in the Philippines. We examined the phylogenetic and phylogeographic relationships of representative CHIKV isolates obtained from the 2012 Philippines outbreak with other CHIKV isolates collected globally. Asian CHIKV isolated from the Philippines, China, Micronesia and Caribbean regions were found closely related, herein denoted as Cosmopolitan Asian CHIKV (CACV). Three adaptive amino acid substitutions in nsP3 (D483N), E1 (P397L) and E3 (Q19R) were identified among CACV. Acquisition of the nsP3-483N mutation in Compostela Valley followed by E1-397L/E3-19R in Laguna preceded the nationwide spread in the Philippines. The China isolates possessed two of the amino acid substitutions, nsP3-D483N and E1-P397L whereas the Micronesian and Caribbean CHIKV inherited all the three amino acid substitutions. The unique amino acid substitutions observed among the isolates suggest multiple independent virus dissemination events. The possible biological importance of the specific genetic signatures associated with the rapid global of the virus is not known and warrant future in-depth study and epidemiological follow-up. Molecular evidence, however, supports the Philippines outbreak as the possible origin of the CACV.